Surface Engineering of C/N/O Functionalized Materials - Zhang, Yanxiang (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book discusses the latest developments in the surface engineering of C/N/O functionalized materials, including both experimental and theoretical studies on heat treatment and surface engineering of metals, ceramics, and polymers.